The Agrobacterium rhizogenes oncogenes rolB and ORF13 increase formation of generative shoots and induce dwarfism in Arabidopsis thaliana (L.) Heynh. (November 2016) - Kodahl, Nete; Müller, Renate; Lütken, Henrik
Highlights: Expression of rol B increases flowering in A. thaliana . Expression of ORF13 causes dwarfism in A. thaliana . ORF13 may be essential for the characteristic phenotype induced by A. rhizogenes . Abstract: Plant transformation with the wild type Ri plasmid T-DNA of Agrobacterium rhizogenes is a promising method for breeding of compact plants and has been the subject of numerous studies. However, knowledge concerning the isolated functions of single genes and ORFs from the plasmid is limited. The rol B and ORF13 oncogenes of A. rhizogenes show considerable promise in plant breeding, but have not been comprehensively studied. Detailed information regarding the morphological impact of specific genes of the Ri plasmid will allow for optimized targeted breeding of plants transformed with the wild type Ri plasmid T-DNA. rol B and ORF13 were recombined into the genome of Arabidopsis thaliana using Gateway ® cloning and the effect on plant growth was assessed biometrically throughout the plants' life cycle. rol B-lines exhibited dwarfing, early necrosis of rosette leaves, altered leaf and flower morphology, and developed an increased number of inflorescences per rosette area compared to the wild type. ORF13-lines were extremely dwarfed, attaining only ca. 1% of the rosette area of the wild type, leaf and flower size was reduced, and the shape modified. The study documents that the traits inferred by the rol B oncogene yield plants with increased formation of generative shoots, but also result in some degree of premature senescence of vegetative organs. The extreme dwarfism seen in ORF13-lines indicate that this oncogene may be more important in the dwarfing response of plants transformed with the wild type Ri plasmid T-DNA than previously assumed and that transformation with this oncogene induces a very compact phenotype.